Measles-Associated CNS Complications: A Review - Jain, Reena; Aulakh, Roosy (Journal of Child Science, 2022)
Measles virus infection is a common infectious disease of childhood, incidence of which is still high in developing countries. Other than the morbidity associated with the acute systemic infection, the measles virus can cause serious fatal neural complications. It can either enter the brain leading to acute encephalitis like primary measles encephalitis and acute post infectious measles encephalomyelitis or it may persist in brain cells (as mutated virus) leading to long-term neurodegenerative diseases like measles inclusion body encephalitis and subacute sclerosing pan encephalitis. The patho-clinical features, treatment, and the outcomes of these complications are different and should be identified in time for early diagnosis and management.
Keywords: measles virus; primary measles encephalitis; acute post infectious measles encephalomyelitis; measles inclusion body encephalitis; subacute sclerosing pan encephalitis